A qualitative interview study on psycho-oncologists’ experiences with patient deaths in Germany - Svenja Wandke; Lisa Brandes; Mareike Rutenkröger; Hannah Führes; Klaus Lang; Martin Härter; Karin Oechsle; Carsten Bokemeyer; Isabelle Scholl (Scientific Reports)
Abstract Despite regular exposure to patient deaths, little research has explored how psycho-oncologists experience and cope with these events. This study examined the unique challenges faced by psycho-oncologists in Germany, aiming to contribute to the broader understanding of professional grief and its impact on healthcare professionals’ mental health and well-being. We conducted 25 semi-structured interviews with psycho-oncologists. The interviews were audiorecorded, transcribed, and analyzed using content analysis. Participants experienced an average of two patient deaths per month. The findings revealed both positive and negative effects of patient deaths on their personal and professional lives. While many participants managed professional grief successfully, most expressed unmet needs for education and information on coping strategies. Peer support was identified as particularly valuable for managing the emotional toll. Overall, patient deaths had significant, varying impacts on psycho-oncologists, highlighting the need for healthcare institutions to implement targeted support and educational interventions to address professional grief and enhance their well-being.